Ethics of Care and Statutory Social Work in the UK: Critical Perspectives and Strengths. Issue 1 (1st January 2018) - Collins, Stewart
Abstract : Definitions of ethics of care are provided and key features outlined. Critical perspectives on ethics of care are explored such as ambiguous meanings, the neglect of surveillance roles in statutory social work, work with reluctant service users, the lack of detailed purpose and goals when considering the relationship between ethics of care, social workers and service users, the possible reinforcement of dependency rather than independence and autonomy. However, ethics of care offer several positives in enabling statutory social work to reclaim its individualistic, 'care' roots, and also in emphasising roles in influencing policy, politics and the struggles for equality at individual and institutional levels. They act as a possible alternative to 'scientific', bureaucratic, organisational procedures, by concentrating on genuine, human relationships that emphasise care. Common, mutual, interdependent bonds between social workers and service users are highlighted, with a focus on caring practices and activities, accompanied by a potential reduction in professional power and role distance. Finally, consideration is given to some implications for social work theories, statutory social work organisations and the importance of care for social workers themselves.